Peran Siamang (Hylobates Syndactylus) Sebagai Pemencar Biji Di Resort Way Kanan Taman Nasional Way Kambas Lampung - Andrian Dwi Atmanto; Bainah Sari Dewi; Nuning Nurcahyani (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Way Kambas National Parklocated inLampung Provinceis habitat for gibbon (H. syndactylus), frugivorous primate which plays a role as seeds dispersal process in tropical rainforests with its activities. Purpose of the research is to determine the gibbon's role as seeds dispersal. It was conducted in August 2012 in the Way Kanan Resort of Way Kambas National Park. The method used is exploration and feces analysis. Based on the research, there are 37 samples of gibbon's feces and 7 spesies of seed plant dispersed by gibbon include Polygonum chinense, Grewia paniculata, Ficus sp, Bouea macrophylla, Dacryodes rostrata, Aporosa aurita, and Aplaia palembanica. Seeds are distributed by gibbon using endozoochory process without destroying seeds and can be dispersed far from the parent trees.Distance of the seed dispersed by gibbons ranges 0-385 meters. Defecation activity of gibbon is done after waking, feeding activity, and when moved to other tree with frequency of defecation between 3-6 times a day. The composition ofgibbon's feces is seeds and leaves. The highest attendance of seeds in feces is Polygonum chinense seeds (42,12%) and the lowest is Aporosa aurita seeds (1,18%). The mean seeds in feces is 7,38 from 273 seeds. Keywords : gibbon, seed dispersal, Way Kambas National Park